2017
DOI: 10.1161/circep.116.004663
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of the Subcutaneous Implantable Cardioverter-Defibrillator

Abstract: Background— Alternative techniques to the traditional 3-incision subcutaneous implantation of the subcutaneous implantable cardioverter-defibrillator may offer procedural and cosmetic advantages. We evaluate 4 different implant techniques of the subcutaneous implantable cardioverter-defibrillator. Methods and Results— Patients implanted with subcutaneous implantable cardioverter-defibrillators from 2 hospitals between 2009 and 2016 were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
52
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 9 publications
10
52
1
Order By: Relevance
“…Implantation of an S-ICD is technically a novel procedure for cardiologists, thus new surgical skills are needed to be mastered [6,23,25,27]. All procedures were successfully performed in our population, which is consistent with the high success rate of S-ICD implantation reported by other authors [15,28].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Implantation of an S-ICD is technically a novel procedure for cardiologists, thus new surgical skills are needed to be mastered [6,23,25,27]. All procedures were successfully performed in our population, which is consistent with the high success rate of S-ICD implantation reported by other authors [15,28].…”
Section: Discussionsupporting
confidence: 86%
“…In combined analysis of the IDE study and EFFORTLESS registry [15] the incidence of primary electrical disease was only 15%, while ischaemic and dilated cardiomyopathy were diagnosed in almost 70% of patients. Papers describing early experience with S-ICD reported that primary prophylaxis of SCD was an indication for high-voltage systems usually in more than half of the patients (50-67%) [21][22][23]25]. The pooled analysis of IDE and the EFFORTLESS registry revealed that 70% of their group were implanted in primary prophylaxis of SCD [15].…”
Section: Discussionmentioning
confidence: 99%
“…The parasternal incisions can be cosmetically less appealing, particularly in women and young patients. Although the procedural duration was longer compared to the conventional technique, this is still a very early experience with the procedure. As with any newly introduced technique, there is a learning curve that needs to be overcome after which the procedure duration is expected to decrease to that like other implantation techniques of S‐ICD …”
Section: Discussionmentioning
confidence: 97%
“…The parasternal incisions can be cosmetically less appealing, particularly in women and young patients. Although the procedural duration was longer compared to the conventional technique, 16 this is still a very early experience with the procedure.…”
Section: Device Infection Risk and Cosmetic Appearancementioning
confidence: 94%
“…The subcutaneous implantable cardioverter‐defibrillator (S‐ICD; Boston Scientific, Marlborough, MA, USA) was developed as an alternative to transvenous (TV) ICDs among patients without the need for pacing. It has been shown to be safe and effective and global adoption is increasing . Much focus has been on the appropriate populations for this device.…”
Section: Introductionmentioning
confidence: 99%